The newborn under phototerapy at a neonatal intensive care unit – the mother’s knowlegde - Georgia Rabelo Pinheiro; Lorena Barbosa Ximenes; Regina Cláudia Melo Dodt; Mônica Oliveira Batista Oriá; Régia Christina Moura Barbosa (Rev Rene)
Hyperbilirubinemia is the most frequent pathology during the neonatal period. This exploratory study aimed at identifying the profile of mothers who have their babies undergoing phototherapy and verifying the mothers’ knowledge about phototherapy with their children attending a Neonatal Intensive Care Unit. Mothers were interviewed during March and April – 2006 in a high and middle risk Neonatal Intensive Care Unit at a Public Hospital. During data collection, a semistructured form was used to approach the mothers’ knowledge about child care during phototherapy. The results highlight the need of an interdisciplinary team to better insert the mother into the therapy process, since guiding mothers throughout the stages of the treatment reduce their anxiety, impotence, and fear, among other feelings, ultimately helping the baby to respond more efficiently to the treatment, as a result of the higher maternal adhesion to the phototherapy.